Key Issues on the Brazilian Foreign Policy - Guedes de Oliveira, Marcos Aurelio (2013)
This paper deals with different views of the Brazilian foreign policy. First, it introduces foreign policy main directives: economic and social development as well as border delimitation with other South American countries. Secondly, it shows the situation of Brazilian relations after the Cold War with the countries and regions of the World: the United States (US), the European Union (EU), Latin America, China, Africa, India and other regions. Finally, it looks at Brazilian national interest in the United Nations (UN) and on the following fields: on energy, on environment and on defense.